Modeling of the photo-response of a smart thin layer chromatography system - Caputo, D.; de Cesare, G.; Nardini, M.; Nascetti, A.; Scipinotti, R. (2011 4th IEEE International Workshop on Advances in Sensors and Interfaces, 2011)
Smart thin layer chromatographic plates integrate thin film photo-sensors for the in-situ real-time monitoring of the chromatographic run, enabling additional functionalities such as precise control of the plate development and additional analytical information on the sample. In order to extract useful information in real-time during the development of a chromatographic plate with integrated photo-sensors an analytical model is proposed based on geometrical optics considerations. The model is then used on experimental data to exemplify its use for gathering additional analytical information on the sample.